Establishment of 6 pediatric rhabdomyosarcoma patient's derived xenograft models closely recapitulating patients' tumor characteristics. Issue 3 (June 2023) - Gasparini, Patrizia; Casanova, Michela; Centonze, Giovanni; Borzi, Cristina; Bergamaschi, Luca; Collini, Paola; Testi, Adele; Chiaravalli, Stefano; Massimino, Maura; Sozzi, Gabriella; Ferrari, Andrea; Moro, Massimo
Introduction: The prognosis for patients with metastatic and recurrent pediatric rhabdomyosarcoma (RMS) remains poor. The availability of preclinical models is essential to identify promising treatments We established a series of pediatric RMS patient derived xenografts (PDXs), all faithfully mirroring primary tumor characteristics and representing a unique tool for clarifying the biological processes underlying RMS progression and relapse. Methods: Fresh tumor samples from 12 RMS patients were implanted subcutaneously in both flanks of immunocompromised mice. PDXs were considered as grafted after accomplishing three passages in mice. Characterization of tumor tissues and models was performed by comparing both morphology and immunoistochemical and fluorescence in situ hybridization (FISH) characteristics. Results: Six PDXs were established, with a successful take rate of 50%. All models closely mirrored parental tumor characteristics. An increased grafting rate for tumors derived from patients with worse outcome (p = 0.006) was detected. For 50% PDXs grafting occurred when the corresponding patient was still alive. Conclusion: Our findings increase the number of available RMS PDX models and strengthen the role of PDXs as useful preclinical tools for patients with unmet medical needs and to develop personalized therapies.